A study on the semantic and lexicogrammatical features of the short story Mr. Know All by W. Somerset Maugham: A systemic functional analysis - Nguyễn, Thị Bích Liên (2017)
Chapter 1: General introductionpresents rationalefor the study, aim of the study, scope of the study, method of the study anddesign of the study. Chapter 2: Theretical backgrounds. provides the theoretical frameworkof the study. Its focus is on introducing important concepts ofsystemic functional linguistics relevant to the topic of the study anda brief introduction to theauthoand the story Mr. Know All Chapter 3: Data analysis–analyses the semanticand lexicogrammaticalfeatures of the story Mr. Know Allto seehowtransitivity, mood & modality, and theme arepatterned in the story and provides commentsbased on these findings. Part III. Chapter 4: Conclusion summarizes what has been studied; provides some implications for teaching and learning English; and makes some suggestions for further research.